The accuracy of judging compared with objective computerised analysis in trampolining - Johns, P. E.; Brouner, J. W. (World Congress of Performance Analysis of Sport IX, 2012)
Five execution judges are used in competitive trampolining to score performance. Athletes perform two routines of ten skills with each skill being judged by the five execution judges (Kunze et al., 2009). With judging being performed in real time subjectivity can falsely deduct marks or miss an imperfect performance due to human error, perspective error or bias. Therefore, using an objective computer analysis system, a true reflection of performance can be measured (Hughes & Franks, 2004; Coalter et al., 1998). Thirteen competitors at a national competition were recorded, sagittal and frontal planes, to allow for routines to be evaluated. All participants were over the age of 18 and gave full informed consent. Judges` also gave consent to participate, however, the true purpose of the study was initially withheld. Judges` scores for each skill and routine were collected post event as to not influence or cause bias. Performance indicators were established via coaching manuals from British Gymnastics and the Code of Practice by the Federation Internationale de Gymnastique (FIG) (British Gymnastics, 2009a, b, c, d; Kunze et al., 2009). Post event analysis was performed by a qualified judge using a statistical video analysis package (GameBreaker Plus, Sports Tec, New Zealand). Results showed no significance difference (p=0.925) between judges` scoring and the post performance computer analysis of the final routine scores. However, the overall competition rankings differed between the judges and post event scores, with a discrepancy between 2nd and 3rd places. Kappa and percentage error scores demonstrated sound reliability of the analyest, 0.99 and 0.1% respectively (Hughes & Franks, 2004; McGinn et al., 2004) To conclude, the current judging system is an accurate method of scoring competitions. However, post analysis of the judges` marks revealed many arithmetic errors showing limitations to the method from human error when analysing in real time. Therefore, aiding judgeing with the addition of computerised methods could increase accuracy. Further research is needed to investigate the reliability of judging panels at competitions to check it is within the limits set by the FIG.